O Direito aplicável aos negócios relativos a instrumentos financeiros: a disciplina introduzida pelo novo Regulamento comunitário sobre a lei aplicável às obrigações contratuais («Roma I») - Matias Fernandez, Maria João (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
One of the novelties of the Rome I Regulation are the special provisions in Articles 4(1)(h) and 6(4)(d) and (e) on the law applicable to contracts related to financial instruments. While the former addresses contracts entered into within a regulated market or a multilateral trading facility, the latter deal with exceptions to the rule on consumer contracts. The papers main goal is to understand the rules set forward by such provisions and, hence, to assess their contribution to the reduction of legal risk.
Keywords: Conflict of laws; «Rome I» Regulation; financial markets; financial instruments